PENGARUH AIR LIMBAH INDUSTRI SUSU TERHADAP PERTUMBUHAN DAN HASIL TANAM TANAMAN BAWANG MERAH (Allium cepa L.) - Arif Yachya (Biota, 2017)
During this time the handling of waste water in dairy industry (ALIS) in Indonesia is done by dumping into the river. This activity causes damage to rice fields which are located around the river flow. The yield losses due to ALIS is up to 50%. The friendly method is needed for handling ALIS. Since ALIS is known to contain beneficial macro nutrients for plants growing so potents as an organic fertilizer. This study aimed to optimize the ALIS concentrations (0, 20, 40, 60, 80 and 100% v / v) for the growth and yield of onion (Allium cepa L.) var. Buto Ijo. The results showed, treatment ALIS 60% (v / v) increasedheight ofonion leaves until 24.45 cm. Whereas ALIS treatment on various concentrations had no effect on the number of onion shoots. The yields showed, the highest of fresh weight of biomass, number of bulbs, fresh weight and dry weight of bulbs per clump approximatly 13.03 g g; 12,33 bulbs, 7.79 g and 5.38 g was achieved by treatment of ALIS 80% (v/v). Based on the result ofgrowth and crop yields, ALIS 80% (v/v) was selected as the optimum concentration for onion crop. The ALIS was given100 mL and three times during the growing season.